Optimation of Red Ginger (Zingiberofficinale Roxb) Extract Lozenges with Various Concentrations of Binding and Disintegrant Materials - Dwi Bagus Pambudi; St. Rahmatullah; Novel Umarella; Hilda Fitria Wulandari; Dewi Safitri (Urecol Journal. Part C: Health Sciences, 2022)
The red ginger plant through several studies is known to have potential as a medicinal plant because it contains oleoresin and flavonoid that can relieve symptoms of coughs and are also effective in curing symptoms of sore throat, especially sore throat. The use of medicinal plants are active ingredients in herbal medicinal preparations has been widely used, especially in tablet preparations. In this study, tablets were formulated in 3 formulations with varying concentrations of binder and disintegrant. The method used in the wet granulation’s method because the selection of the method is adjusted to the nature of the extract and excipients to be used. Based on the tablet evaluation results, it was shown that the 3 formulas only met the requirements for the size uniformity test and the disintegration time test.